2020
DOI: 10.1126/scitranslmed.aax9276
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial in a dish using iPSCs shows lovastatin improves endothelial dysfunction and cellular cross-talk in LMNA cardiomyopathy

Abstract: Mutations in LMNA, the gene that encodes lamin A and C, causes LMNA-related dilated cardiomyopathy (DCM) or cardiolaminopathy. LMNA is expressed in endothelial cells (ECs); however, little is known about the EC-specific phenotype of LMNA-related DCM. Here, we studied a family affected by DCM due to a frameshift variant in LMNA. Human induced pluripotent stem cell (iPSC)–derived ECs were generated from patients with LMNA-related DCM and phenotypically characterized. Patients with LMNA-related DCM exhibited clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 65 publications
2
62
0
Order By: Relevance
“…This step sorts the iECs from the transdifferentiation protocol. CD144, also known as VE-Cadherin has been widely used for the isolation of ECs derived from embryonic stem cells (ESCs) and iPSCs ( Liu et al., 2020 ; Sayed et al., 2020 ; Sayed et al., 2015 ). Aspirate the spent medium and dissociate the cells using 1 mL TrypLE express per well for 10 mins at 37°C.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…This step sorts the iECs from the transdifferentiation protocol. CD144, also known as VE-Cadherin has been widely used for the isolation of ECs derived from embryonic stem cells (ESCs) and iPSCs ( Liu et al., 2020 ; Sayed et al., 2020 ; Sayed et al., 2015 ). Aspirate the spent medium and dissociate the cells using 1 mL TrypLE express per well for 10 mins at 37°C.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…We recommend dedicating 2-wells for each downstream phenotypic characterization. The most widely used assays to assess the function of ECs are listed here: a) In vitro angiogenesis assay to assess the capacity to form network of tubular structures; b) Nitric oxide assay to assess the capacity to produce NO; c) Acetylated LDL-uptake assay to assess the capacity to uptake Ac-LDL; d) In vitro scratch assay to assess the migration capacity; e) In vivo angiogenesis assay to assess the capacity to from capillaries ( Huang et al., 2021 ; Liu et al., 2018 ; Paik et al., 2018 ; Sayed et al., 2020 ; Zhang et al., 2019b ).…”
Section: Expected Outcomesmentioning
confidence: 99%
“…Crosstalk between myocytes and non-myocytes are essential for maintaining a physiological balance and cardiovascular tone. Endothelial cells support cardiac metabolism, contractility and survival ( Brutsaert, 2003 ; Sayed et al, 2020 ); whereas fibroblast play a key role in metabolic, structural, electrical and mechanical maturation ( Giacomelli et al, 2017 ; Giacomelli et al, 2020 ). Therefore, it is intuitive that these major non-myocyte cell populations may play a significant role in disease and drug-related toxicities.…”
Section: Building Physiologically Relevant In Vitro mentioning
confidence: 99%
“…To further enrich ECs, the differentiated cells can be sorted for the CD31 positive population ( Liu et al, 2018a ). In a recent study from our lab, we demonstrated that iPSC-ECs exhibit a wide range of properties characteristic of primary ECs ( Sayed et al, 2020 ). Specifically, iPSC-ECs showed morphological similarity to primary ECs with a cobblestone cell shape.…”
Section: Human Ipsc-based Vascular Modelmentioning
confidence: 99%